Heavy-duty Casting Robot Trajectory Planning Based on the Law of Composite Polynomial Motion - Wang Chengjun; Yang Lin; Li Long; Shen Yuzhe (Jixie chuandong)
In order to further improve the stability and accuracy of the pouring trajectory of the heavy-duty casting robot during the pouring operation, a new hybrid four-degree-of-freedom heavy-duty casting robot is taken as the research object, and a trajectory planning method based on the synthesis of the fifth-order polynomial and the sinusoidal acceleration motion law is proposed. The degree-of-freedom of the actuator is calculated by the topological structure theory of the robot mechanism, and the position of the parallel mechanism is solved by the closed-loop vector method, the kinematic position equation of the hybrid mechanism is derived according to the equivalent method and the geometric method. The trajectory planning of the robot is carried out by combining the fifth-order polynomial and the sinusoidal acceleration motion law. The Adams software is used to simulate the trajectory motion of the robot end, and the parameters obtained by the theoretical solution are verified. The results show that the trajectory based on the combination of the fifth-order polynomial and the sine acceleration motion law is smoother and more natural than the fifth-order polynomial, and the maximum speed of the robot end is reduced by 14%, avoiding the vibration due to excessive speed fluctuations.